Primary cutaneous cryptococcosis – History, concepts, clinical and therapeutic update - Marques, Sílvio Alencar [UNESP]; Camargo, Rosangela Maria Pires de [UNESP] (Elsevier, 2025)
Cryptococcosis is a disease caused by fungi of the genus Cryptococcus, with the species Cryptococcus neoformans and Cryptococcus gattii being recognized as pathogenic. Cutaneous cryptococcosis can be classified as “secondary”, developing from a previous systemic disease, or, on the contrary, “primary”, resulting from transcutaneous inoculation of the agent. It can also be classified as “disseminated cutaneous cryptococcosis”, when there is an associated systemic disease, or “localized”, when it is restricted to the skin. This article uses the term “primary cutaneous cryptococcosis” because it is the most widely used and already established in the literature. Historically, the first report of a possible case of primary cutaneous cryptococcosis (PCC) occurred in 1950 by Gancy WM and was published in the Archives of Dermatology and Syphilology. Subsequently, the rare and sporadic reports in the following decades were reviewed and reported in the 1985 publication by Baes & van Cutsen. However, the unequivocal acceptance of the existence of PCC as a distinct disease only occurred in 2003 with the publication by Neville S et al. of the French Cryptococcosis Study Group. The fundamental criterion established to consider it as PCC was the proven absence of systemic disease, whether pulmonary, in the CNS or other location at the time of diagnosis of the cutaneous condition, characterized by a single lesion and, mostly, in an exposed area. These and other clinical criteria, diagnostic confirmation, and therapeutic choice are discussed in detail in the full text.
Keywords: Clinical medicine; Cryptococcosis; Cryptococcosis/diagnosis; Cryptococcosis/therapy; Mycology